Graphene based nanocomposites for alloy (SnO2), and conversion (Fe3O4) type efficient anodes for Li-ion battery applications - Mhamane, Dattakumar; Aravindan, Vanchiappan; Taneja, Divya; Suryawanshi, Anil; Game, Onkar; Srinivasan, Madhavi; Ogale, Satishchandra B. (Composites Science and Technology, 2016)
Two types of trigol reduced one pot synthesized graphene (TRG) based nanocomposites (SnO2-TRG, and Fe3O4-TRG) are examined as potential anodes for Lithium ion battery (LIB) applications. The two specific systems represent different electrode reaction mechanisms, namely alloying, and conversion respectively. The high resolution transmission electron microscopy (HR-TEM) analysis confirms the uniform distribution of SnO2 (similar to 2 nm), and Fe3O4 (similar to 8 nm) particulates on ultrathin TRG nanosheets and highlights the importance of surfactant free synthesis. The SnO2-TRG, and Fe3O4-TRG exhibited the maximum reversible capacity of similar to 947, and similar to 1024 mA h g(-1), respectively. The results show that such graphene based composite materials can be effectively used as prospective anodes for LIB applications. (C) 2016 Elsevier Ltd. All rights reserved.